Stimulating interest in civil engineering through the introduction of ETABS software at SMA Negeri 3 Jakarta - Fahmy Hermawan; Bambang Endro Yuwono; Ruwaida Zayadi; Ulfa Fatmasari Faisal; Lucia Helly; Salwa Zahra Rizkina; Muhammad Yusuf (Universitas Muhammadiyah Magelang, 2024)
The rapid advancement of construction technology, particularly the use of ETABS software, demands a competent and adaptive workforce. This community service aimed to introduce students of SMA Negeri 3 Jakarta to ETABS technology, providing them with a solid foundation for entering the construction industry. The activity was conducted through direct demonstrations of ETABS software and a questionnaire to measure participants' understanding and interest. The results showed a significant increase in students' understanding of civil engineering concepts, particularly structural analysis. Furthermore, students' interest in the field of civil engineering also increased. This is evidenced by the survey results from 25 participants, where 60% of students expressed interest in learning more about ETABS software and pursuing a career in civil engineering.